Metal complexes of a homopolymer system containing diethanolamine side group: synthesis and dielectrical behaviors - Acikses, Aslisah; Comez, Necmittin; Biryan, Fatih (Taylor & Francis Inc, 2019)
In this work, 4-diethanolaminomethyl styrene (DEAMSt) monomer was prepared by modification of 4-chloromethyl styrene with diethanolamine. The homopolymerization of styrene modificated was carried out by free radical polymerization method at 60 degrees C in presence of 1,4-dioxane and AIBN. The metal complexes were prepared by reaction of the homopolymer used as ligand P(DEAMSt)L-l and Ni(II), Co(II) metal ions in presence of ethanol and dilute NaOH at 65 degrees C for 48 h in pH 6. The structure of modificated monomer, homopolymer used as ligand and polymer-metal complexes were characterized by (FT-IR), H-1-NMR, C-13-NMR, Raman spectroscopy tecniques, elemental analysis, SEM, XRD and magnetic measurements. Their geometric structures according to magnetic measurements of Co(II) and Ni(II) complexes were estimated that have a tetrahedral structure. P(DEAMSt)L-l polymer has a transition state between amorphous and crystalline, whereas metal complexes (Co(II) and Ni(II) are with a large crystal structure. The molecular weight of P(DEAMSt)L-1 homopolymer was determined by gel permeation chromatography (GPC). The glass transition temperature (Tg) of homopolymer was measured by differantial scanning calorimeter (DSC). The thermal behaviors of both ligand and polymer-metal complexes were investigated by thermogravimetric analysis (TGA) and (DTA). The results obtained were compared with each other. Then, the dielectrical measurements (dielectric constant, dielectric loss and conductivity) of the ligand and polymer-metal complexes were investigated as a function of temperature and frequency. The activation energies (Ea) of the ligand and metal complexes were determined from the conductivity measurements.
Keywords: Dielectrical behavior; ligand; metal complexes; metal ions; conductivity